Bar fracture of implant-retained overdenture: Protocol of a systematic review and meta-analysis - Stanek, J.; Riad, A.; Slezakova, S.; Azar, B.; Klugarova, J.; Pokorna, A.; Klugar, M. (Journal of Osseointegration, 2021)
Aim The fractured bar is a common prosthetic complication that deteriorates the patient€™s experience and prosthesis functionality; therefore, we aim to determine risk factors, prevalence, and incidence of bar fracture. Methods We will conduct a systematic review using the guidelines of Cochrane€™s Handbook and Joanna Briggs Institute€™s (JBI) Manual and will adhere to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). A three-step search strategy will be conducted to retrieve interventional and observational studies from biomedical bibliographic databases as well as grey literature. Two authors will assess the retrieved studies according to the predefined eligibility criteria. Data collection will be conducted using Extraction Forms. Risk of bias of included interventional studies will be assessed using the Risk of Bias 2 tool, while observational studies will be evaluated by ROBINS-E. Studies findings will be qualitatively and quantitively synthesized using JBI SUMARI. Results The results of this systematic review will be presented to clinicians and researchers in speciality conferences and a peer-reviewed journal. Conclusion This review is the first to identify the clinical and biological risk factors of bar fracture and to evaluate its prevalence and incidence rates; aiming to provide evidence-based recommendations for treatment planning and maintenance of implant-retained overdenture using bar-clip attachment system.